Effectiveness Test of Sapodilla Leaf Extract (Manilkara Zapota L.) Concentration 75% and 85% as Root Canal Irrigation Material in Inhibiting The Growth of Bacteria Enterococcus Faecalis - Maya Sari Dewi; I Gusti Ngurah Bagus Tista; Ni Komang Santhi Hari Pertiwi (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: Root canal irrigation is an important step in supporting the success of root canal treatment. The most resistant microorganism and often found in case after root canal treatment is Enterococcus faecalis. Sapodilla leaf contain a secondary metabolites of flavonoids, saponins, tannins, phenol, alkaloids and steroids which act as antibacterial. Natrium hipoklorit with a concentration of 2,5% is used for effective root canal irrigation solution. The purpose of this study was to determine the inhibitory power present in sapodilla leaf seeds against Enterococcus faecalis. Material and Methods: This research is a experimental laboratory with Post Test Control Group Design. The sample used was a bacterial Enterococcus faecalis which was divided into 4 groups, namely the group treated with sapodilla leaf with concentrations of 75% and 85%, the group treated with NaOCl 2,5% as a positive control, and the group treated with aquadest as negative control, with 6 repetitions each. Sapodilla leaf extraction was carried out by maceration method using 96% ethanol solvent. Results and Discussions: Inhibition zone test was carried out using the Kirby Bauer method. Using aquadest as negative control and natrium hipochloride as positive control so the inhibition power produced at 75% extract concentration was 11,09 mm and at 85% concentration was 13,28 mm,which is the positive control as higher category. Conclusion: It can be concluded that the inhibitory power of sapodilla leaf extract (Manilkara Zapota L) with the most effective concentration in the treatment group containing sapodilla leaf with a concentration of 85%.